Ministerial Decree No. 274/2014 amending ministerial decree No. 209/2009 promulgating the executive regulation of the law organizing the tourism companies / translated by The middle east library for economic services. - The middle east library for economic services, translator. (2025)
Ministry of tourism decree no. 274 of the year 2014 issued on 20/3/2014 وزارة السياحة قرار رقم 274 لسنة 2014 صادر بتاريخ 20/3/2014